UJI EFEKTIVITAS LOSIO EKSTRAK DAUN KEMANGI (Ocimum sanctum Linn.) SEBAGAI REPELAN TERHADAP NYAMUK BETINA - Isnindar Isnindar; Willy Hervianto; Liza Pratiwi (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2012)
Kemangi (Ocimum sanctum Linn.) is a plant that has the chemical content of essential oils are linalool, estragol, graniol, eugenol, and cineol. The purpose of this research is to know whether extract of kemangi leaves have a effect as mosquito repellent and how about its effectivity when it was formulated in lotion product. Extract test group being used are negative control, n-heksane extract, and methanol extract. Lotion group test being used are negative control, positive control, Lotion A (lotion that contain 2,5 % n-heksane extract) Lotion B (lotion that contain 5% n-heksane extract) Lotion C (lotion that contain 10% n-heksane extract). Effectiviy test was done for six hour with test for 15 minutes every single hour. It was done in three time repetition on one people. Stability test carried out for 31 days includes organoleptic, viscosity, ability of spreading and sticking and pH. The results shows that n-heksane extract give the best repellent effect than methanol extract so it was formulated in lotion product with different concentration. The results of the effectivity test and stability test was analized statistically by use One Way ANOVA with confidence level 95% and then it analized with Post Hoc Tukey. The result repelensi percentages are Lotion A (53,97%), Lotion B (69,67%), Lotion C (85,97%). The results shows that Lotion C give the best repellent effect between Lotion A and Lotion B. The result shows that Lotion C has a few change in all variables of stability test, so Lotion C better than Lotion A and Lotion B.